2015
DOI: 10.3945/jn.114.198945
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Hemoglobin Disorders Rather Than Iron Deficiency Are a Major Predictor of Hemoglobin Concentration in Women of Reproductive Age in Rural Prey Veng, Cambodia,

Abstract: Multiple biomarkers for anemia and iron deficiency were significantly influenced by the presence of hemoglobin disorders, hence reducing their diagnostic sensitivity. Further investigation of the unexpectedly low prevalence of IDA in Cambodian women is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 42 publications
9
86
1
Order By: Relevance
“…Further, as more than 80% of women reported taking an IFA supplement at the time of the survey, the lack of association between IFA supplementation and Hb concentration was unexpected. Though we did not measure biochemical markers of iron status (e.g., serum ferritin, transferrin saturation, and soluble transferrin receptor), the weak associations between IFA and Hb concentration and IFA and anemia in our study support the growing evidence 11,12 that iron deficiency may not be the primary cause of anemia in Cambodian women.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Further, as more than 80% of women reported taking an IFA supplement at the time of the survey, the lack of association between IFA supplementation and Hb concentration was unexpected. Though we did not measure biochemical markers of iron status (e.g., serum ferritin, transferrin saturation, and soluble transferrin receptor), the weak associations between IFA and Hb concentration and IFA and anemia in our study support the growing evidence 11,12 that iron deficiency may not be the primary cause of anemia in Cambodian women.…”
Section: Discussionsupporting
confidence: 68%
“…In a study involving 420 non-pregnant women in Prey Veng Province, Karakochuk and others 11 found that more than half of the women had a genetic hemoglobinopathy (predominantly Hb E variants and α-thalassemia). Further, only 2% had low iron stores (ferritin < 15 μg/L) and the prevalence of iron deficiency anemia was ∼14% in women with a hemoglobinopathy, compared to only ∼1.5% in women without a hemoglobinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Deworming treatment in both groups likely minimized the risk of anemia due to helminth infection. The randomized design of the study controlled for unmeasured confounders such as genetic hemoglobin disorders, which are known to contribute to anemia in Cambodian women (34).…”
Section: Discussionmentioning
confidence: 99%
“…1 (31). These disorders can also cause anemia, so it's important to know the cause of anemia in order to determine proper treatment.…”
Section: The Way Forwardmentioning
confidence: 99%